Treatment of Crohn's disease with recombinant human interleukin 10 induces the proinflammatory cytokine interferon γ. Issue 2 (1st February 2002) - Tilg, H; van Montfrans, C; van den Ende, A; Kaser, A; van Deventer, S J H; Schreiber, S; Gregor, M; Ludwiczek, O; Rutgeerts, P; Gasche, C; Koningsberger, J C; Abreu, L; et al.
Abstract : Background: Interleukin 10 (IL-10) exerts anti-inflammatory actions by counteracting many biological effects of interferon γ (IFN-γ). Aims: To investigate this in humans, we studied the effects of human recombinant IL-10 administration on IFN-γ production by patient leucocytes. Furthermore, we assessed the IFN-γ inducible molecule neopterin and nitrite/nitrate serum levels, which are indicative of endogenous nitric oxide formation. Methods: As part of two placebo controlled double blind studies, we analysed patients with chronic active Crohn's disease (CACD) who received either subcutaneous recombinant human IL-10 (n=44) or placebo (n=10) daily for 28 days, and patients with mild to moderate Crohn's disease (MCD) treated with either subcutaneous IL-10 (n=52) or placebo (n=16) daily for 28 days. Neopterin and nitrite/nitrate concentrations were measured in serum, and ex vivo IFN-γ formation by lipopolysaccharide or phytohaemagglutinin (PHA) stimulated whole blood cells were investigated before, during, and after IL-10 therapy. Results: In patients with CACD, the highest dose of 20 μg/kg IL-10 caused a significant increase in serum neopterin on days +15 and +29 of therapy compared with pretreatment levels. No changes were observed for nitrite/nitrate levels under either condition. In MCD, treatment with 20 μg/kg IL-10 resulted in a significant increase in PHA induced IFN-γ production. Conclusions: High doses of IL-10 upregulate the production of IFN-γ and neopterin. This phenomenon may be responsible for the lack of efficacy of high doses of IL-10 in the treatment of CACD and MCD.